Beginning data science in R 4: data analysis, visualization, and modelling for the data scientist - Mailund, Thomas (California : Apress, 2022)
Discover best practices for data analysis and software development in R and start on the path to becoming a fully-fledged data scientist. This book teaches you techniques for both data manipulation and visualization and shows you the best way for developing new software packages for R. -- Provided by publisher.
Introduction to R programming -- Reproducible analysis -- Data manipulation -- Visualizing data -- Working with large datasets -- Supervised learning -- Unsupervised learning -- More R programming -- Advanced R programming -- Object oriented programming -- Building an R package -- Testing and package checking -- Version control -- Profiling and optimizing.
Includes index.
Catalography
Keywords: R (Computer program language); Quantitative research; Computer software -- Development; COMPUTERS / Databases; COMPUTERS / Programming Languages; Computer software -- Development; Quantitative research; R (Computer program language)